Habit and Identity: Behavioral, Cognitive, Affective, and Motivational Facets of an Integrated Self - Verplanken, Bas; Sui, Jie (Frontiers in Psychology, 2019)
Two studies investigated associations between habits and identity, in particular what people consider as their 'true self'. Habit-identity associations were assessed by within-participant correlations between self-reported habit and associated true self ratings of 80 behaviors. The behaviors were instantiations of 10 basic values. In Study 1, significant correlations were observed between individual differences in the strength of habit-identity associations, measures of cognitive self-integration (prioritizing self-relevant information), self-esteem, and an orientation toward an ideal self. Study 2 further tested the assumption that habits are associated with identity if these relate to important goals or values. An experimental manipulation of value affirmation demonstrated that, compared to a control condition, habit-identity associations were stronger if participants explicitly generated the habit and true self ratings while indicating which values the behaviors would serve. Taken together, the results suggest that habits may serve to define who we are, in particular when these are considered in the context of self-related goals or central values. When habits relate to feelings of identity this comes with stronger cognitive self-integration, higher self-esteem, and a striving toward an ideal self. Linking habits to identity may sustain newly formed behaviors and may thus lead to more effective behavior change interventions.